Authenticities: Philosophical Reflections on Musical Perfomance - Kivy, Peter 1934-2017 (London Cornell University Press, 1995)
In his latest book on the aesthetics of music, Peter Kivy presents an argument not for authenticity but for authenticities of performance, including authenticities of intention, sound, practice, and the authenticity of personal interpretation in performance. . . . As usual, Kivy's work is beautifully written, well argued, and provocative."-Notes"Kivy has provided a sorely needed framework for all future discussion of the authenticity matter. This is his best book, a major contribution to performance studies and to musical aesthetics; likely it will be studied and cited for generations."-Choice"Written in lively prose, with a keen sense of reality, [this volume] ought to be of interest not only to philosophers and musicologists, but to all serious lovers of music."-Roger Scruton, Times Literary Supplement"The consistent theme running through Kivy's book is the need for interpretation as the personal authenticity and authority of the performer against the ideology both of the composer as genius and of the puritanical devotion to the authority of the text of the early music devotees. . . . This is a most valuable book, one which constantly surprises and delights through its philosophical insights and informed musical understanding."-British Journal of Aesthetics
Keywords: Music philosophy and esthetics; Performance